Class-home Connection Using Communication Technology and its Impact on Anxiety Reduction and Academic Performance - Liqaa Habeb Al-Obaydi; Zainab Abbas Jawad; Fathu Rahman (مجلة الآداب, 2022)
This study tries to shed light on the importance of using communication technology in class-home connection, where the two-way communication that requires electronic interactive dialogue between teachers and parents are used, and how this communication may enhance students’ English language academic performance and help in reducing their classroom anxiety. The sample of the study consists of thirty EFL secondary school students with their parents. Two instruments were used to collect data; structured interview with parents, observation checklists to measure students’ anxiety, in addition to use students’ academic performance to determine their level of achievement in English. The results show that parents have positive attitudes towards using communication technology in class-home connection. It further demonstrates that students’ level of anxiety was reduced notably after applying the experiment, when the parents connect with the teacher daily, in addition to palpable improvement in students’ academic performance in English language.